Diversity and community structure of anaerobic gut fungi in the rumen of wild and domesticated herbivores - Meili, Casey H.; TagElDein, Moustafa A.; Jones, Adrienne L.; Moon, Christina D.; Andrews, Catherine; Kirk, Michelle R.; Janssen, Peter H.; J. Yeoman, Carl; Grace, Savannah; Borgogna, Joanna-Lynn C.; Foote, Andrew P.; Nagy, Yosra I.; et al. (Applied and environmental microbiology, 2024)
Ruminants are highly successful and economically important mammalian suborder. Ruminants are herbivores that digest plant material with the aid of microorganisms residing in their GI tract. In ruminants, the rumen compartment represents the most important location where microbially mediated plant digestion occurs, and is known to house a bewildering array of microbial diversity. An important component of the rumen microbiome is the anaerobic gut fungi (AGF), members of the phylum Neocallimastigomycota . So far, studies examining AGF diversity have mostly employed fecal samples, and little is currently known regarding the identity of AGF residing in the rumen compartment, factors that impact the observed patterns of diversity and community structure of AGF in the rumen, and how AGF communities in the rumen compare to AGF communities in feces. Here, we examined the rumen AGF diversity using an amplicon-based survey targeting a wide range of wild and domesticated ruminants ( n = 206, 15 different animal species) obtained from 15 different countries. Our results demonstrate that while highly diverse, no new AGF genera were identified in the rumen mycobiome samples examined. Our analysis also indicate that animal host phylogeny, diet, biogeography, and domestication status could play a role in shaping AGF community structure. Finally, we demonstrate that a greater level of diversity and higher inter-sample variability was observed in rumen compared to fecal samples, with two genera ( Neocallimastix and Orpinomyces ) present in higher abundance in rumen samples, and two others ( Cyllamyces and Caecomyces ) enriched in fecal samples. Our results provide a global view of the identity, diversity, and community structure of AGF in ruminants, elucidate factors impacting diversity and community structure of the rumen mycobiome, and identify patterns of AGF community variability between the rumen and feces in the herbivorous GI tract.